El Excentrico, 1954-09-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
September 5, 1954 [5 de septiembre de 1954]. Ano 4, No. 21. Cover contains a photo of Tin-Tan y su carnal Marcelo (transl: Tin-Tan and his friend Marcelo), who were holding a show on the day of this issues release. Their live performance took place at the Civic Auditorium.